Neural Crest Stem Cells from Dental Tissues: A New Hope for Dental and Neural Regeneration - Gaskon Ibarretxe; Olatz Crende; Maitane Aurrekoetxea; Victoria García-Murga; Javier Etxaniz; Fernando Unda (Hindawi Limited, 2012)
Several stem cell sources persist in the adult human body, which opens the doors to both allogeneic and autologous cell therapies. Tooth tissues have proven to be a surprisingly rich and accessible source of neural crest-derived ectomesenchymal stem cells (EMSCs), which may be employed to repair disease-affected oral tissues in advanced regenerative dentistry. Additionally, one area of medicine that demands intensive research on new sources of stem cells is nervous system regeneration, since this constitutes a therapeutic hope for patients affected by highly invalidating conditions such as spinal cord injury, stroke, or neurodegenerative diseases. However, endogenous adult sources of neural stem cells present major drawbacks, such as their scarcity and complicated obtention. In this context, EMSCs from dental tissues emerge as good alternative candidates, since they are preserved in adult human individuals, and retain both high proliferation ability and a neural-like phenotype in vitro. In this paper, we discuss some important aspects of tissue regeneration by cell therapy and point out some advantages that EMSCs provide for dental and neural regeneration. We will finally review some of the latest research featuring experimental approaches and benefits of dental stem cell therapy.